Concept of Light And Its Mystical And Philosophical Essence In Boborahim Mashrab's Work "Mabdai Nur" - Badriddinova, Nilufar (Buletin Antropologi Indonesia, 2025)
In the article, “light” is a mystical concept, the universe is full of light, and the light is the light of the world. Mabdayi nur is the place of origin of light, and as a category of Islamic philosophy, light is the divine truth, its teaching about divine light representing religious knowledge, and the role of not only the soul, but also the body in the manifestation of divine light in a person is special. focused. The philosophical analysis of the mystical concepts in the work "Mabdai Nur" by Boborahim Mashrab is justified to be of great importance in instilling in our people the spirit of striving for humanity, respect for our national values, and an honest way of life.